Combination of Multilocus Sequence Typing and GS‐PCR Reveals an Association of Pandemic Vibrio parahaemolyticus Clone with Clinical and Seafood Isolates. Issue 10 (5th September 2018) - Zhou, Min; Chen, Wanyi; Shi, Chunlei; Wang, Hongxun; Shi, Xianming
Abstract : Abstract: Vibrio parahaemolyticus is a global leading cause of seafood‐borne bacterial gastroenteritis. Clinical, seafood, and environmental V. parahaemolyticus isolates from the eastern coast of China were analyzed for their virulence, and for phenotypic and molecular traits. The frequency of pandemic isolates was 50.9% among clinical isolates and 42.8% among seafood isolates as confirmed by group‐specific polymerase chain reaction (GS‐PCR). Serological analysis indicated that O3:K6, O1:K25, O1:KUT, O3:K68, and O4:K68 were the predominant serotypes among these pandemic isolates. It is worth noting that the pandemic serotypes were not exclusively identified from clinical samples. Rather, they were also isolated from seafood samples. It was also shown by multilocus sequence typing (MLST) typing that isolates from clinical (59), seafood (28), and environmental samples (18) were grouped into 17, 23, and 17 sequence types (STs), respectively. We updated 17 STs in the MLST database. ST‐3 and ST‐189 were the dominant ones among clinical isolates. Interestingly, ST‐3 was also the most abundant among seafood isolates, and represented a significant risk to food safety due to the clear association with tdh and the GS‐PCR marker. A minimum‐evolution (ME) tree generated from the concatenated sequences of the 7 loci of the 54 STs uncovered phylogenetic relationships between seafood and clinical isolates. The MLST results also indicated a high degree of nucleotide diversity in recA that had the greatest influence on the phylogenetic relationships. Our findings provided new insight into the phylogenic relationship among pandemic V. parahaemolyticus isolates from various samples and enhanced the MLST database as well as microbiological risk assessment. Practical Application: Pandemic V. parahaemolyticus isolates have become a serious public health concern. This study demonstrated the characteristics of clinical and seafood V. parahaemolyticus isolates, and determined the phylogenetic relatedness among them. These results can be used for microbiological risk assessment in China.